1964
DOI: 10.1620/tjem.84.201
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Activity of Digest Products of Fibrinogen by Plasmin

Abstract: Degradation products having various grades of molecular weight were derived from fibrinogen by plasmin action. A highly purified anticoagulant active substance was obtained by the combined use of ammonium sulfate fractionation and column chromatography on DEAE-cellulose. This sub stance has the ability to inhibit completely the clotting of whole blood in a concentration of 1-1.5%, to prolong the thrombin clotting time, and to produce a macroscopically and interference-phase-contrast-microscopically abnormal cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1967
1967
1971
1971

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
1
2
0
Order By: Relevance
“…Fibrinogen degradation products when measured in the presence of thrombin or thrombin Ca renders the results unreliable, especially on longer incubation times. This corresponds with experiments of Maki et al (29) using the TEG which were confirmed by Hirsch et al (30). The heat precipitation method gave an almost complete recovery, whether the split products were of high or low concentration.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fibrinogen degradation products when measured in the presence of thrombin or thrombin Ca renders the results unreliable, especially on longer incubation times. This corresponds with experiments of Maki et al (29) using the TEG which were confirmed by Hirsch et al (30). The heat precipitation method gave an almost complete recovery, whether the split products were of high or low concentration.…”
Section: Discussionsupporting
confidence: 88%
“…Niewiarowski and Kowalski as well as Triantaphyllopoulos noted first that split products are coagulation inhibitors. It is generally agreed that fraction E is primarily an inhibitor of thrombin formation, whereas, fraction D inhibits fibrinogen-fibrin conversion, producing defective fibrin polymerisation (29,31 ). Whether the coagulation inhibitory (antithrombin) effect is heat labile or stable is under discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of the anticoagulant effect of plasmindegraded fibrinogen in 1957 (Niewiarowski & Kowalski), the effect of the split products on the clotting mechanism has received much attention in the literature. Some authors believe that the split products have an antithrombin effect (Niewiarowski & Kowalski 1958, Triantaphyllopoulos 1959, Triantaphyllopoulos & Triantaphyllopoulos 1966; others, that they inhibit polymerization of the fibrin monomer (Alkjaersig et al 1962, Latallo et al 1962 or that they can both inhibit polymerization of the fibrin monomer and act as an antithrombin (Latallo et al 1964, Maki et al 1964, Triantaphyllopoulos 1961. A thermostabile split product (E product?)…”
mentioning
confidence: 99%